In response to "white hands": Nicholas, Land Cooper, S (eds) (1990) Psychology and Apartheid: Essays on the struggle for psychology and the mind in South Africa. Johannesburg: A Vision/Madiba Publication. - Pillay, Yogan (PINS-Psychology in Society, 2026)
Psychology and Apartheid, contains edited versions of some of the papers that were delivered at the Psychology and Apartheid Conference which was held at the University of the Western Cape in March 1989. The conference set out to articulate the ways in which psychology was used historically, in South Africa, to perpetuate domination of the majority by the minority white regime. The tone of the conference (and which is reflected in the book) was one of outrage, in the first instance, and an attempt, in the second to begin a discourse that would respond to the perceived needs of the majority of South Africans.